Age-related changes in skeletal muscle mitochondria: the role of exercise - Dae Yun Seo; Sung Ryul Lee; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Jin Han (Integrative Medicine Research)
Aging is associated with mitochondrial dysfunction, which leads to a decline in cellular function and the development of age-related diseases. Reduced skeletal muscle mass with aging appears to promote a decrease in mitochondrial quality and quantity. Moreover, mitochondrial dysfunction adversely affects the quality and quantity of skeletal muscle. During aging, physical exercise can cause beneficial adaptations to cellular energy metabolism in skeletal muscle, including alterations to mitochondrial content, protein, and biogenesis. Here, we briefly summarize current findings on the association between the aging process and impairment of mitochondrial function, including mitochondrial biogenesis and reactive oxygen species in skeletal muscle. We also discuss the potential role of exercise in the improvement of aging-driven mitochondrial dysfunctions.